Gamson–Modigliani Framing Analysis on Cin(T)a and 3 Hati 2 Dunia 1 Cinta - Deavvy M.R.Y Johassan (Jurnal Komunikasi dan Bisnis, 2023)
The journey of the national film industry has a long history. Gradually, the film industry has become a mere commercial industry dominated by horror and comedy films. This has resulted in the formation of stereotypes that all national films have the same content and do not vary. The films "cin(T)a" and "3 Hati 2 Dunia 1 Cinta" present as new variations in national cinema, which carry the unusual theme of religious pluralism. Gamson and Modigliani's framing analysis sees mass media discourse as consisting of a number of packages to form the construction of an event. There are two aspects to framing. First, choose reality. Second, how the media presents that reality. Gamson and Modigliani's framing analysis consists of two elements: framing devices and reasoning devices. The research method used in this study is descriptive qualitative method. Descriptive qualitative methods produce up-to-date data that can be used in the development of science. The results of this study found that the films "cin(T)a" and "3 Hati 2 Dunia 1 Cinta" portray religious pluralism as a beautiful thing, and people should be able to live in harmony and comfort despite differences in society, but it does not deny that although the two films try to show the relationship between religions from a positive side, the relationship between religions is still something that cannot be accepted by some people. Based on the results of the study, the author concludes that religious pluralism is a beautiful thing in the lives of Indonesian people. However, many things must be considered if religious pluralism is associated in the context of romance, especially to the marriage ladder.